215 The Impact of Intraoperative MRI and Other Factors on Survival for Patients With Newly Diagnosed Glioblastoma. A Multicenter Assessment of Over 800 Patients. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Shah, Amar S; Sylvester, Peter; Vellimana, Ananth K; Dunn, Gavin P; Evans, John; Jensen, Randy L; Honeycutt, John H; Sutherland, Garnette R; Cahill, Daniel P; Shah, Mitesh V; Abram, Steven R; Oswood, Mark C; et al.
Abstract: INTRODUCTION: Intraoperative magnetic resonance imaging (iMRI) has been shown to increase rates of gross total resection and overall survival in glioblastoma (GBM) in a series of smaller observational and randomized studies. This study aims to assess parameters affecting survival and other outcomes for patients undergoing craniotomy for newly diagnosed GBM including the impact of iMRI. METHODS: Analysis of a multicenter retrospective/prospective REDCaptm database of over 7500 patients undergoing cranial neurosurgical procedures with or without iMRI at 8 North American centers (1996-2016). Eight-hundred eleven patients were identified who had undergone surgery for newly diagnosed GBM, including 315 surgical resections with iMRI, 348 without iMRI, 148 others, including biopsies and laser interstitial thermotherapy. Kaplan-Meier analysis and Cox-regression models were used to assess survival. iMRI was performed using a movable ceiling-mounted high-field magnet at the discretion of the operating surgeon. RESULTS: The use of iMRI trended toward an increased median overall survival (OS) from 14.67 to 17.33 mo ( P = .18), with an increased proportion receiving gross total resection (GTR, 32.39% vs 41.35%, P = .03; OR = 1.479 [1.033, 2.117]). Univariate and multivariate analysis identified the following as correlated with increased (OS): surgical resection versus biopsy, younger age, American Society of Anesthesiologists (ASA) classification, O6-methylguanin-DNA-methyltransferase (MGMT) promoter methylation, use of adjuvant chemoradiation, and clinical trial participation. For patients with IDH-1 mutations, iMRI increased progression-free survival (median 6.967 mo non-iMRI vs greater than 36 mo iMRI, P = .008) and trended toward increased OS (median 14.67 mo vs greater than 36 mo, P = .34). CONCLUSION: Large multicenter database analysis of newly diagnosed GBMs suggests that use of iMRI during resection increases rates of GTR and may increase OS. Age, ASA status, MGMT promoter methylation, adjuvant chemoradiation, and clinical trial participation are predictors of improved OS. iMRI may be most impactful in patients with IDH-1 mutations.